Introduction - Pupo, Norene (Just Labour: A Canadian Journal of Work and Society, 2009)
Takes note of the Open Statement signed by over 120 scholars on unionization and economic and social well-being of Canadian. Introduces the theme: of the issue: the U.S. Employee Free Choice Act and its implications for Canada, including critical reviews of Anne Layne-Farrar's argument that unionization has undermined Canadian labour market performance.